Smooth braneworld models possibility in modified gravities - Brito, G. P. de [UNESP]; Hoff da Silva, J. M. [UNESP]; Silva, P. Michel L. T. da [UNESP]; Souza Dutra, A. de [UNESP] (World Scientific Publ Co Pte Ltd, 2015)
In this paper, it is shown that the consideration of the braneworld consistency conditions within the framework of bulk modified gravities allows for the existence of thick branes in the five-dimensional case with compact extra dimension. On studying the specific consistency conditions in the Brans-Dicke gravity, we were able to show that the brane generating scalar field potential is relevant for relaxing the gravitational constraints.
Keywords: Braneworld; modified gravities; sum rules